2012
DOI: 10.1038/ajh.2012.87
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pulse Pressure Is Associated With the Localization of Coronary Artery Disease Based on Coronary Flow Lateralization

Abstract: Hypertension has a major impact on cardiovascular and renal mortality and morbidity, with a 90% lifetime risk of developing hypertension. 1 Optimal blood pressure control reduces the risk of stroke by 38% and of myocardial infarction by 16%. 2 Compared to peripheral arterial pressure measurements, aortic pressures were shown to better predict coronary artery disease (CAD) 3,4 and cardiovascular risk. 5 Brachial arterial pressure does not correctly reflect aortic pressure, especially its systolic component, due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In addition, since the characteristics of animal tissue can vary with age, weight and so on, it is hard to standardize animal models for reliable and reproducible data. Moreover, it is challenging to aptly evaluate injury to the aorta, which is characterized by high blood pressure and active pulsation 16,17 , in models, which brings about issues of reliability and reproducibility of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since the characteristics of animal tissue can vary with age, weight and so on, it is hard to standardize animal models for reliable and reproducible data. Moreover, it is challenging to aptly evaluate injury to the aorta, which is characterized by high blood pressure and active pulsation 16,17 , in models, which brings about issues of reliability and reproducibility of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic changes in the intramural tension have recently been recognized an important factor in the pathogenesis of atherosclerosis and acute coronary syndromes. 1 The study by Khoueiry et al 2 fits well into list of recent research investigating the relation between BP, arterial stiffness, and atherosclerosis. 3,4 Nowadays, there is no doubt about the presence of significant relation between the pulsatile BP component and atherosclerosis, but these links are in fact bidirectional.…”
mentioning
confidence: 82%
“…1 A number of studies have shown the correlation between central PP and the extent of coronary atherosclerosis. 5 In the population studied by Khoueiry et al 2 aortic PP was higher in subjects with right coronary artery (RCA) stenosis compared to those with stenosis in the left coronary artery (LCA). This could be due to the difference in blood flow pattern between LCA and RCA (as suggested by Khoueiry et al 2 ) or earlier (at lower level of BP) atherosclerotic plaque development in LCA compared to RCA.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…AS has been associated with numerous comorbidities and, most importantly, shown to independently predict all-cause and cardiovascular mortality, fatal and nonfatal coronary events and fatal strokes, both in the general and CKD populations [12][13][14][15][16] . Increased left ventricular stress and reduced coronary perfusion, both caused by AS, lead to cardiac hypertrophy and myopathy, thus resulting in congestive heart failure and sudden death in CKD patients.…”
Section: Thyroid Hormonesmentioning
confidence: 99%